The Influence of Service Quality and Brand Image on Purchase Decisions: Study on Consumers of Muslim Fashion Products in Bandung City - Firza Insanudzaky; Muhammad Rayyan Arasyi; Muhammad Zacky Alfasyah; Vanezza Sayyid Akbar (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
Good management is essential to a business because it directly affects the company's operations. Goods management aims to maintain the efficiency and productivity of the company. This study aims to analyze the goods management system at a Manufacturing Company in Tangerang City, which is essential for this company. The research method used was an online interview via chat, giving twelve questions to the company regarding goods management. The study results show that the goods management system in one of the Manufacturing Companies in Tangerang City has many benefits in reducing the risk of losing goods and streamlining work. In its implementation, one of the Manufacturing Companies in Tangerang City uses Axapta and ODDO software which specifically can oversee the management of goods effectively. In its implementation, companies also need to carry out established procedures and provide training to their employees. Overall, this study provides recommendations to one of the Manufacturing Companies in Tangerang City to continuously develop an existing goods management system and Manufacturing Companies in Tangerang City to provide more budget to train and change technology according to current needs to improve effectiveness and efficiency in the goods management system to monitor the inventory and usage of goods.